Sanksi Pidana terhadap Pelaku Penculikan Anak - Ardi Putra Dewa Agung; I Made Sepud; A.A. Sg. Laksmi Dewi (Jurnal Preferensi Hukum, 2020)
Kidnapping is an act committed by someone without the right for the purpose of enabling such person under the powers of the kidnappers. An abductor targets child as a victim. Based on the online news website liputan6.com, Chairman of the National Commission for Child Protection Arist Merdeka Sirait said the Child Abduction case continues to increase from 2014 to 2017. The issues regarding the case to be examined in the present study are: (1) The regulation regarding criminal liability of offenders of child abduction, (2) The criminal sanction and condemnation towards the offenders of child abduction. From the results of an exploration conducted with the normative research method in this study it was found that the criminal liability of the offenders of child abduction is regulated in Article 76F Indonesian Law No. 35 of 2014 concerning the Amendment towards the Law No. 23 of 2002 concerning Child Protection. The kidnapping of a child may be held to criminal liability if the offender has committed an act fulfilling the elements of delinquency. Regarding criminal sanctions and condemnation against child abductors who are proven guilty of legally and convincingly in the eyes of the law of committing the crime of kidnapping of a child can be sentenced in the form of imprisonment and a fine penalty. Criminalization of child abductors depends on the role of the judge who examines and prosecutes the case. Judges are given the freedom to set the type of criminal, criminal conduct, or the high and low criminal.